Extraction Of Flavonoid, Phenolic, And Saponin In Shallot Skin (Allium Cepa Var. Aggregatum) For Antibacterial Application - Muhammad Triyogo Adiwibowo; Shintasya Tiara Firliyani; Nurul Ma'rifah; Nufus Kanani; Wardalia Wardalia; Alia Badra Pitaloka; Marta Pramudita (CHEMICA: Jurnal Teknik Kimia, 2023)
Shallot skin (Allium cepa var. aggregatum) contains secondary metabolites of flavonoid, phenolic, and saponin that can be antibacterial. This research was conducted by extracting the shallot skin using maceration and ultrasound-assisted methods with 3, 5, and 7 days for maceration extraction and 10, 20, and 30 minutes for ultrasonication-assisted extraction (UAE). The extract was then tested for phytochemical screening and analysis of its flavonoid, phenolic, and saponin levels. Three extracts with the best secondary metabolite compounds were then tested for the inhibitory power of the extracts against Escherichia coli through the diffusion method. The results showed that shallot skin extract contained flavonoid and phenolic compounds but not saponin. Based on the analysis of the levels of these compounds using UV-Vis spectrophotometry, three extracts with the highest flavonoid and phenolic content were obtained from maceration extraction for seven days, the UAE method for 20 minutes, and the UAE extraction method for 30 minutes. The extract using the UAE method has relatively higher flavonoid and phenolic content (6.93 and 2.59 ppm, respectively) than the extract using the maceration method (5.48 and 2.46 ppm, respectively), which is also considered more efficient in terms of time. A preliminary antibacterial activity test showed antibacterial activity in the shallot skin.